2015
DOI: 10.1016/j.cellsig.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Differential submitochondrial localization of PINK1 as a molecular switch for mediating distinct mitochondrial signaling pathways

Abstract: Mutations in mitochondrial kinase PINK1 cause Parkinson disease (PD), but the submitochondrial site(s) of PINK1 action remains unclear. Here, we report that three-dimensional structured illumination microscopy (3D-SIM) enables super-resolution imaging of protein submitochondrial localization. Dual-color 3D-SIM imaging analysis revealed that PINK1 resides in the cristae membrane and intracristae space but not on the outer mitochondrial membrane (OMM) of healthy mitochondria. Under normal physiological condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…A recent study employing 3D structured illumination super‐resolution microscopy suggested that under physiological conditions, a PINK1‐GFP fusion protein is localized in the cristae membrane and intracristae space (Fallaize et al . ), however, it is not known whether the GFP fusion might affect the submitochondrial localization of PINK1. Although some aspects of PINK1 mitochondrial import and processing have been elucidated, several issues are still unclear.…”
Section: The Mitochondrial Localization Of Pink1mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study employing 3D structured illumination super‐resolution microscopy suggested that under physiological conditions, a PINK1‐GFP fusion protein is localized in the cristae membrane and intracristae space (Fallaize et al . ), however, it is not known whether the GFP fusion might affect the submitochondrial localization of PINK1. Although some aspects of PINK1 mitochondrial import and processing have been elucidated, several issues are still unclear.…”
Section: The Mitochondrial Localization Of Pink1mentioning
confidence: 99%
“…At the outer mitochondrial membrane, PINK1 interacts with the TOM complex, dimerizes, and is activated by autophosphorylation (Lazarou et al 2012;Okatsu et al 2012Okatsu et al , 2013Hasson et al 2013;Aerts et al 2015a). A recent study employing 3D structured illumination super-resolution microscopy suggested that under physiological conditions, a PINK1-GFP fusion protein is localized in the cristae membrane and intracristae space (Fallaize et al 2015), however, it is not known whether the GFP fusion might affect the submitochondrial localization of PINK1. Although some aspects of PINK1 mitochondrial import and processing have been elucidated, several issues are still unclear.…”
Section: The Mitochondrial Localization Of Pink1mentioning
confidence: 99%
“…In contrast, other studies reported significant levels of PINK1 protein under normal conditions, but localized PINK1 to either the OMM with its kinase domain facing the cytoplasm [ 36 38 ] or to the IMM/IMS with its kinase domain facing the IMS [ 39 43 ]. Recently, super-resolution imaging analyses using three-dimensional structured illumination microscopy (3D-SIM) [ 44 ] or a combination of tracking and localization microscopy (TALM) and fluorescence photoactivation localization microscopy (F-PALM) [ 45 ] clearly showed that, under normal conditions, PINK1 is not present on the OMM of healthy mitochondria, but rather PINK1 resides in the IMM/IMS where it is mainly localized to the cristae membrane and intracristae space. Furthermore, PINK1 was found to colocalize with the mitochondrial chaperone TRAP1, a previously identified PINK1 substrate [ 40 , 46 ], in these submitochondrial compartments [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Super-resolution imaging analyses showed that, in response to mitochondrial depolarization, PINK1 changes its submitochondrial localization from the IMM/IMS to the OMM of depolarized mitochondria [ 44 , 45 ], whereas TRAP remains in the IMM/IMS [ 44 ]. The PINK1 localization on the OMM of depolarized mitochondria is likely due to the blockade of PINK1 mitochondrial import through the IMM by the loss of mitochondrial membrane potential [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological conditions, PINK1 is colocalized with its substrate TRAP1 in the cristae membrane and intracristae space. In response to mitochondrial depolarization, PINK1, but not TRAP1, translocates to the OMM, suggesting that differential submitochondrial localization of PINK1 serves as a molecular switch mediating two distinct mitochondrial signaling pathways to maintain mitochondrial homeostasis (Fallaize et al 2015). Following this observation, it may be informative to define whether mutations in PINK1 affect the function of TRAP1 in stress-induced neuronal death.…”
Section: Neurodegenerative Disorders: Pdmentioning
confidence: 99%